Arquitetura e espiritualidade : Suger (1081-1151) e a edificação do gótico - Neves, Tainah Moreira (2016)
This master dissertation analyses the relation between the Architecture and the Spirituality in the rebuilding of the Abbey of Saint-Denis (1130/1137-1144) led by Abbot Suger (1081- 1151), based on the remaining physical structure of the church and on his